2014
DOI: 10.1161/circulationaha.113.003863
|View full text |Cite
|
Sign up to set email alerts
|

Deep RNA Sequencing Reveals Dynamic Regulation of Myocardial Noncoding RNAs in Failing Human Heart and Remodeling With Mechanical Circulatory Support

Abstract: Background: Microarrays have been used extensively to profile transcriptome remodeling in failing human heart, although the genomic coverage provided is limited and fails to provide a detailed picture of the myocardial transcriptome landscape. Here, we describe sequencing-based transcriptome profiling, providing comprehensive analysis of myocardial mRNA, microRNA (miRNA) and long non-coding RNA (lncRNA) expression in failing human heart, before and after mechanical support with a left ventricular assisted devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
350
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(382 citation statements)
references
References 41 publications
23
350
3
6
Order By: Relevance
“…P < 0.01) might lead to loss of some true positive, novel lncRNAs. Comparing these 145 differentially expressed lncRNAs to 679 lncRNAs differentially expressed in ICM patients in an earlier study, 13 we found that 19 were dysregulated in both studies. Genome browser views of representative differentially expressed lncRNAs are shown in Figure 2C.…”
Section: The Expression Of Lncrnas Is Altered In Icmmentioning
confidence: 67%
See 3 more Smart Citations
“…P < 0.01) might lead to loss of some true positive, novel lncRNAs. Comparing these 145 differentially expressed lncRNAs to 679 lncRNAs differentially expressed in ICM patients in an earlier study, 13 we found that 19 were dysregulated in both studies. Genome browser views of representative differentially expressed lncRNAs are shown in Figure 2C.…”
Section: The Expression Of Lncrnas Is Altered In Icmmentioning
confidence: 67%
“…In that study, the investigators profiled lncRNA expression from paired non-ischemic and ischemic human failing left ventricles before and after left ventricular assist device (LVAD). 13,31 The authors suggested that lncRNAs could be used to discriminate failing hearts of different pathologies. Interestingly, another recent study identified a novel circulating lncRNA, LIPCAR, as a molecular marker for HF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1) were shown to contribute to muscle or myocardial function (8, 9). miRNAs and other classes of RNA have been profiled in failing human myocardium (10)(11)(12)(13)(14)(15)(16)(17), and a selected subset was also investigated as circulating biomarkers in HF (18)(19)(20)(21)(22)(23)(24). However, in these studies heart tissue and circulating miRNA abundance changes were not acquired simultaneously to correlate changes in tissue versus circulating miRNA composition.…”
mentioning
confidence: 99%